EVALUATION OF DRUG PROCUREMENT AND AVAILABILITY AT HADJI BOEJASIN HOSPITAL, PELAIHARI 2006 – 2008 - Anna Apriyanti; Ibnu Gholib Gandjar; Satibi Satibi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug procurement system in H Boejasin Hospital, Tanah Laut regency showed over stock that have been existed since 2006. This problem may cause poor availability and inefficiency of drug procurement. The aim of this research is to evaluate drug procurement system concerning drug availability and efficiency at Hadji Boejasin Hospital. This was a qualitative descriptive study, which support used secondary data and observation of drug storage warehouse as well as depot of hospital pharmacy. Subject of the study consisted of two groups: procurement group and user group. Result of the study showed that the process of drug procurement using local expenditure and revenue fund of Tanah Laut regency at Hadji Boejasin Hospital from 2006 ‐ 2008 had been based on the President Decree No. 80/2003 through selective tender and negotiated purchase. Result of the evaluation showed that: 1) period of drug procurement was 1‐3 month; 2) frequency of drug procurement was 1 2 time/year; 3) procurement procedure was based on some standardized phases. The procurement system caused highly damaged/expired drugs (0,48‐1,90%), highly non prescribed drugs (5,98%‐ 11.11%), drugs were out of stock (1‐10 month), and low annual turn over ratio (TOR). TOR value in 2006 was 1.28; in 2007 was 0.40, in 2008 was 0.36, which meant that drug circulation in warehouse was relatively low. Based on these study, it can be concluded that level of drug availability and efficiency at Hadji Boejasin Hospital using procurement system of local expenditure and revenue fund of Tanah laut regency in 2006–2008 was not good enough. Keywords : drug procurement system, drug availability